2019
DOI: 10.1097/jbr.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Advances in cochlear implantation for hereditary deafness caused by common mutations in deafness genes

Abstract: The pathogenic factors of deafness are complex; more than 50% of cases are caused by genetic factors. Between 75% and 80% of cases of hereditary hearing impairment are autosomal recessive, 15% to 25% are autosomal dominant, and 1% to 2% are mitochondrial or X-linked. Cochlea implantation is the main method for treating severe and extremely severe bilateral sensorineural deafness and it is widely used in clinical treatment. As clinical cases of cochlea implantation accumulate, differences in the efficacy of imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…MYO7A* MYO7A -Motor/Anchor protein Stereocilia Associated with improved results in Usher syndrome but age is most prognostic factor in CI performance with early CI achieving satisfactory auditory and speech outcomes (Xiong et al, 2019) Case study: CI significantly improved speech perception tests [monosyllable: 77%; word: 84%, sentence: 100% (Usami et al, 2020)].…”
Section: Myo15a -Motor Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…MYO7A* MYO7A -Motor/Anchor protein Stereocilia Associated with improved results in Usher syndrome but age is most prognostic factor in CI performance with early CI achieving satisfactory auditory and speech outcomes (Xiong et al, 2019) Case study: CI significantly improved speech perception tests [monosyllable: 77%; word: 84%, sentence: 100% (Usami et al, 2020)].…”
Section: Myo15a -Motor Proteinmentioning
confidence: 99%
“…Tips of stereocilia, organ of corti, lateral wall, and SGN 4/7 patients with poor CI outcomes had bi-allelic PCDH15 mutations; outcomes were worse in CAP, SIR, and speech perception scores Limitations: Small sample size (n = 4) and homogenous population limit generalizability . (Xiong et al, 2019) IHCs and immature OHCs, required for synaptic exocytosis at ribbon synapses (Roux et al, 2006) Important mutation leading to auditory neuropathy spectrum disorder (ANSD). 10 ANSD patients (age 1-5 years old) with OTOF mutations with stable hearing at, 89.0 ± 12.3 dBHL and absent ABR at 95 dBHL before surgery.…”
Section: Pcdh15mentioning
confidence: 99%
See 1 more Smart Citation
“…270 CI is more effective for the patients having a defect in hair cells or the afferent synapses in-between hair cells and auditory nerves, but it is less effective for the auditory nerve defect. 271 For the high-frequency sensorineural deafness, Electro-acoustic stimulation (EAS) shows better results. 272 For EAS, a hearing aid is added with cochlear implants, which acoustically amplifies the low frequency of sound.…”
Section: Current Management and Treatment Optionsmentioning
confidence: 99%
“…278 It has been reported that patients with pathogenic variants in GJB2, OTOF, TMPRSS3, CDH23, SLC26A4, MYO7A, MYO15A, MYTH9, ACTG1, COCH gene show better results with Cochlear implants. 271 Thus, elucidation of the role of multiple genes that play an important role in the etiology of monogenic NSHL shall be helpful in deciding most appropriate management and treatment strategy. It is also desired to have gene variant data from various populations worldwide so as to provide genetic counseling and offer prenatal diagnosis accordingly.…”
Section: Current Management and Treatment Optionsmentioning
confidence: 99%